2021
DOI: 10.1038/s41588-021-00889-w
|View full text |Cite
|
Sign up to set email alerts
|

Genome-scale screens identify factors regulating tumor cell responses to natural killer cells

Abstract: To systematically define molecular features in human tumour cells which determine their degree of sensitivity to human allogeneic natural killer (NK) cells, we quantified the NK cell responsiveness of hundreds of molecularly-annotated "DNA-barcoded" solid tumour cell lines in multiplexed format and applied genome-scale CRISPR-based gene editing screens in several solid tumour cell lines to functionally interrogate which genes in tumour cells regulate the response to NK cells. In these orthogonal studies, NK-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 46 publications
0
54
0
Order By: Relevance
“…Selinexor is currently being assessed in a clinical trial in combination with anti-CD20 antibodies for patients with advanced B cell non-Hodgkin lymphoma (NCT03147885) and HLA-E downregulation by selinexor may therefore contribute to ADCC in this setting. A recent study identified that HLA-E suppresses NK cell sensitivity to tumor cells and that resistance to immune checkpoint blockade therapy in multiple clinical studies correlates with an NK sensitivity gene signature, including HLA-E ( 51 ). This data indicates that therapies which can stimulate NK activation, for example by disruption of NKG2A:HLA-E interactions, may overcome immune checkpoint blockade resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Selinexor is currently being assessed in a clinical trial in combination with anti-CD20 antibodies for patients with advanced B cell non-Hodgkin lymphoma (NCT03147885) and HLA-E downregulation by selinexor may therefore contribute to ADCC in this setting. A recent study identified that HLA-E suppresses NK cell sensitivity to tumor cells and that resistance to immune checkpoint blockade therapy in multiple clinical studies correlates with an NK sensitivity gene signature, including HLA-E ( 51 ). This data indicates that therapies which can stimulate NK activation, for example by disruption of NKG2A:HLA-E interactions, may overcome immune checkpoint blockade resistance.…”
Section: Discussionmentioning
confidence: 99%
“…B7H6 interacts with NK cells through the surface receptor NKp30, and the interaction plays an important role in NK cellrelated immune responses (10). Sheffer et al found that knocking out B7H6 from the surface of colorectal adenocarcinoma decreased the cytotoxicity of primary NK cells (38). Downregulation of cell-surface B7H6 expression on tumor cells also impaired tumor recognition by NK cells, helping tumor cells escape from NK cell-mediated killing (39).…”
Section: Discussionmentioning
confidence: 99%
“…Viral infections can lead to the accumulation of CD56 dim CD16 + NKG2A +/- NKG2C +/- FcRγ -/low NK cells, yet the molecular mechanisms regulating FcRγ levels are not well defined. As this adaptor protein regulates the function of NKp30, NKp46, and CD16, which are shown to take part in anti-viral responses, cancer immunosurveillance, and tumor rejection, it is important to better characterize the mechanism of FcRγ regulation 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Human cytomegalovirus (HCMV) infection can lead to the expansion of a subset of mature CD56 dim CD16 + CD57 +/- FcRγ -/low NK cells that exhibit stable population frequencies over years 6,7 . Reduced FcRγ levels in mature CD56 dim CD16 + can be associated with lower surface NKp30 and NKp46 levels, which may lead to reduced NK cell responses against tumors expressing ligands for these activating receptors 811 , yet have a minor influence on CD16 expression in vivo 5 . Moreover, CD56 dim CD16 + FcRγ -/low NK cells exhibit a higher CD16-mediated response, possibly due to its exclusive association with the CD3ζ homodimer or the CD57 phenotype 4,12,13 .…”
Section: Introductionmentioning
confidence: 99%